Adaptasi teknologi pengering terowongan hohenheim aceh energi matahari pada ukm produsen Pliek U di Aceh Besar (Adaptation of type hohenheim aceh solar tunnel dryer for Pliek U industry in Aceh Besar) - Khathir, Rita; Hartuti, Sri; Yunita, Yunita (Buletin Pengabdian, 2021)
The purpose of this community service activity is to adapt the Hohenheim Aceh tunnel dryer technology for solar energy, to help Small and Medium Enterprises (SMEs) produce Pliek U in Aceh Besar District to increase productivity and quality of Pliek U produced. This community service was conducted in several steps including a survey, focus group discussion with targeted people, designing the dryer, constructing the dryer, training the producers, and dissemination. Results of this program are constructing 3 unit type Hohenheim Aceh solar tunnel dryers for 3 producers, management entrepreneurship training, improvement of packaging and application of digital management, and marketing of the product by using the Qasirs application. In conclusion, the performance of this dryer is very good, namely, it can speed up the drying process while increasing the quality of the Pliek U produced.